Self-rectifying bio memristor and preparation method thereof

CN121728980BActive Publication Date: 2026-10-16DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610196093.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-11
Publication Date
2026-10-16
Estimated Expiration
2046-02-11

AI Technical Summary

Technical Problem

丝蛋白是一种结构可调、环保的生物材料,有望成为实际应用的生物忆阻器构筑材料,但目前用生物基材料构筑自整流忆阻器的案例很少,且用丝蛋白材料构筑功能层的自整流忆阻器尚无研究

Benefits of technology

[0047] (1) The preparation method of the present invention is simple, easy to operate and low in cost. The self-rectified biomemristor obtained has the advantages of high rectification ratio and good stability, and realizes the self-rectification characteristics of high rectification ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121728980B_ABST
    Figure CN121728980B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of semiconductors, and discloses a self-rectifying bio-memristor and a preparation method thereof. The self-rectifying bio-memristor comprises a bottom electrode layer, a memristor functional layer and a top electrode layer which are sequentially compounded. The bottom electrode layer is a PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) film, the memristor functional layer is an SP (silk protein)@Ag + film, and the rectification ratio of the self-rectifying bio-memristor is 1.3×10 3 ~1.7×10 4 under the condition that the limiting current is 0.1 mA and the voltage test range is-2.0~2.0 V. The preparation method comprises the following steps: firstly, spin-coating SP@Ag + solution on one side surface of the PEDOT:PSS film, then performing ethanol immersion and drying to form an SP@Ag + film, and finally depositing an Ag electrode layer on the SP@Ag + film to obtain the self-rectifying bio-memristor. The preparation method is simple and easy to implement, and the obtained self-rectifying bio-memristor can inhibit the leakage current problem of bio-based memristors in high-density integration and realize high rectification ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor technology and relates to a self-rectified bio-memristor and its preparation method. Background Technology

[0002] With the development of artificial intelligence and the rapid growth of the Internet of Things, massive amounts of data are being generated. Due to the limitations of the von Neumann architecture, traditional von Neumann architecture devices are unable to meet data processing demands, making the development of high-density, low-power, and low-cost data storage and information processing technologies an inevitable trend.

[0003] Memristors integrate storage and computation, eliminating data transfer between storage and processing units and significantly reducing latency and power consumption in data processing. Typical memristors have a simple stacked structure, making them easy to integrate at high density and showing great potential to replace traditional storage-computing devices. However, leakage current issues can cause data distortion and additional power consumption during read / write operations, hindering the construction of high-density and ultra-large-scale parallel memristor arrays.

[0004] Integrating diodes and memristors into a single device is one of the effective strategies for solving the aforementioned problems and obtaining high-density integrated memristor arrays. Among them, the 1T1M structure, in which a transistor (T) and a memristor (M) are connected in series, can solve the leakage current problem, but the transistor occupies a large area, which offsets the density advantage of the memristor.

[0005] Self-rectified memristors, due to their inherent characteristics, do not require additional series transistors, simplifying circuit structure, reducing power consumption, increasing integration density, and effectively reducing manufacturing complexity and cost, making them ideal devices for constructing high-density integrated memristor arrays. However, memristors that have achieved self-rectification are mainly based on inorganic materials and some organic materials. These materials have problems such as being difficult to degrade and having poor biocompatibility, which limits their application in fields such as bioelectronics and implantable devices.

[0006] Reference 1 (Nat Commun, 2017, 8: 15666.) describes the room-temperature fabrication of a fully CMOS (Complementary Metal-Oxide-Semiconductor) compatible, all-silicon-based self-rectifying memristor using fluid-supported silicon film transfer technology. The formation and rupture of silicon-rich conductive channels within the silicon oxide layer dominate the RS (resistance switching) behavior, and self-rectification characteristics are achieved through an embedded diode composed of pn electrodes, resulting in a rectification ratio (RR) of 10. 5 .

[0007] In reference 2 (NPG Asia Mater, 2018, 10: 1097-1106.), Pt / TaO was prepared. y / NP TaO x / Ta four-layer self-rectified memristor, through NP TaOx Oxygen vacancy migration within the layer dominates RS behavior, via Pt and TaO. y (Layer thickness ≥ 8 nm) Schottky contacts are formed to achieve self-rectification characteristics, with a rectification ratio (RR) of 10. 4 .

[0008] Reference 3 (Nanomaterials, 2020, 10: 2159.) describes the preparation of Pt / HfO2 / TaO2. x A self-rectifying memristor with a / TiN structure, via HfO2 / TaO x The defect sites dominate the RS behavior by trapping / detrapping electrons, via HfO2 / TaO. x The asymmetric potential barrier of the double layer and the difference in electrode work function together achieve the self-rectification characteristic.

[0009] Reference 4 (IEEE Electron Device Lett., 2021, 42: 1599-1602.) describes a physical transient self-rectifying memristor with a Mo / MgO / AZO / W structure. The RS behavior is dominated by the formation / fracture of oxygen vacancy conductive filaments in the MgO layer. Under negative bias, in the LRS (low resistance state), the Schottky barrier between the AZO depletion region and MgO needs to be overcome; in the HRS (high resistance state), hopping conduction (electron hopping between defect sites) is required. Both significantly suppress reverse current, achieving self-rectification with a rectification ratio (RR) of 10. 2 .

[0010] Reference 5 (Nat Commun, 2022, 13: 574.) describes the fabrication of a single-phase self-rectified memristor based on van der Waals ferroic material CuInP2S6 (CIPS), utilizing controllable Cu... + The synergistic effect of ion migration and the interfacial Schottky barrier enables continuous control of current rectification behavior, exhibiting 10 3 The self-rectification ratio.

[0011] Reference 6 (Nanoscale Horiz., 2022, 7: 299-310.) developed a multifunctional memristor based on an Ag / CIS / Mo structure. By adjusting the thickness and stability of the Ag conductive filament using different experimental parameters, the memristor achieves switching between volatile and non-volatile characteristics. Self-rectification is achieved through the Schottky barrier at the Ag / CIS interface, with a rectification ratio (RR) of 4.0 × 10⁻⁶. 4 .

[0012] Reference 7 (Adv Elect Materials, 2022, 8: 2200702.) developed a self-rectifying memristor based on an Al / AlN / W structure. The RS behavior is achieved through the formation / fracture of nitrogen vacancy conductive wires, and the self-rectification characteristics are achieved through the asymmetric Schottky barrier at the Al / AlN interface. The rectification ratio is significantly improved from 94 to 2600 by reducing the device size from 10 μm to 5 μm.

[0013] Reference 8 (Advanced Materials, 2024, 36: 2406608.) developed a self-rectifying memristor array based on a β-Bi2SeO5 / Bi2O2Se heterostructure. The self-rectifying memristor characteristics are achieved through the synergistic effect of the Schottky barrier and oxygen vacancies, with a rectification ratio RR > 10. 5 .

[0014] Reference 9 (Adv Funct Materials, 2025, 35: 2423880.) developed a Pt / TaO-based method. x A self-rectified volatile memristor with a / TiN (PTT) structure, through TaO x Intralayer oxygen ion migration enables RS behavior via Pt / TaO x with TaO x The / TiN interface forms an asymmetric Schottky barrier, achieving self-rectification characteristics with a rectification ratio RR > 10. 3 .

[0015] Reference 10 (Nat Commun, 2025, 16: 5759.) developed a method based on TiN / HfO. x / Pt structure self-rectifying memristor, HfO is reduced through rapid thermal annealing. x The oxygen vacancy concentration in the layer prevents the formation of continuous conductive filaments to ensure stable rectification characteristics, through HfO x Oxygen vacancy migration within the layer enables RS behavior, based on the difference in work function between TiN and Pt, in TiN / HfO x With Pt / HfO x The interface forms an asymmetric Schottky barrier to achieve self-rectification characteristics, with a rectification ratio RR > 10. 8 .

[0016] Reference 11 (Materials Today Advances, 2025, 28: 100624.) developed a pH-responsive biomemristor based on an Ag / polyethylene glycol lipoic acid (PTAO-Li) / FTO structure. This memristor guides the cationic conductivity of Ag through the CS bonds in the PTAO-Li functional layer. +Migration achieves RS behavior by inhibiting Ag through the formation and breakage of metal-oxygen coordination bonds at different voltages. + The migration achieves self-rectification characteristics, but the rectification ratio is not higher than 30.

[0017] Reference 12 (ACS Appl. Electron. Mater., 2025, 7: 2075-2083) uses an all-solution method to prepare PEDOT:PSS-based self-rectifying memristors, where the RS behavior is dominated by the redox reaction of PEDOT. Self-rectification characteristics are achieved through bias-induced migration of ionic PSS chains within the functional layer, with a rectification ratio (RR) of 30.1.

[0018] However, although self-rectified memristors were successfully constructed in references 1-10 above, and the rectification ratio RR > 10, 2 However, all of them use inorganic materials; while in references 11 and 12, although organic materials are used to construct self-rectifying memristors, the rectification ratios are low and there is a lot of room for improvement in device performance.

[0019] Biomaterial-based memristors possess significant advantages in the field of neuromorphic computing due to their excellent biocompatibility, biodegradability, and sustainability. Silk fibroin is a structurally tunable and environmentally friendly biomaterial that holds promise as a building material for practical bio-memristors. However, there are currently very few cases of constructing self-rectifying memristors using biomaterials, and there is no research on constructing self-rectifying memristors with functional layers using silk fibroin materials.

[0020] Therefore, researching a self-rectified bio-memristor and its fabrication method to suppress leakage current problems and achieve high rectification ratios in high-density integration of bio-based memristors is of great significance for expanding the application fields of bio-based memristors. Summary of the Invention

[0021] The purpose of this invention is to solve the problems existing in the prior art and to provide a self-rectified biomemristor and its preparation method.

[0022] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0023] A self-rectified bio-memristor comprises a bottom electrode layer, a memristor functional layer, and a top electrode layer sequentially composited. The bottom electrode layer is a PEDOT (poly(3,4-ethylenedioxythiophene)):PSS (polystyrene sulfonate) film, and the memristor functional layer is SP@Ag. + membrane;

[0024] SP@Ag + Membrane refers to Ag + Doped SP (silk fibroin) membrane; SP is silk fibroin (SF) or spider silk fibroin (SSP).

[0025] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.60 to 1.20V, the reset voltage is 0.30 to 0.64V, and the low-resistance state resistance is 5.0 × 10⁻⁶. 3 ~4.2×10 4 Ω, high-resistance state resistance is 2.0×10 7 ~4.1×10 8 Ω, rectification ratio is 1.3×10 3 ~1.7×10 4 .

[0026] The self-rectified bio-memristor described in this invention has advantages such as low operating voltage and high self-rectification ratio, and meets the requirements of low power consumption and high-density integration.

[0027] As a preferred technical solution:

[0028] As described above, a self-rectified bio-memristor, SP@Ag + The crystallinity of the membrane is 52.0~57.8%.

[0029] The self-rectified bio-memristor described above has an Ag electrode as its top electrode layer.

[0030] The self-rectified bio-memristor described above has a top electrode layer thickness of 100~120 nm, a memristor functional layer thickness of 60~90 nm, and a bottom electrode layer thickness of 0.9~1.2 μm.

[0031] This invention also provides a method for fabricating a self-rectified bio-memristor as described above, firstly by spin-coating SP@Ag onto one side surface of a PEDOT:PSS film. + The solution was then soaked in ethanol and dried to form SP@Ag. + The membrane, finally in SP@Ag + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane; the immersion time in ethanol was 30-60 min, within which SP@Ag was obtained. + The crystallinity of the film is relatively high, between 52% and 57.8%. With further extension of the soaking time, the crystallinity of the SP film does not change much. The increased crystallinity is beneficial to improving the cycle stability of the memristor.

[0032] SP@Ag + Ag in solution + The concentration is 0.001~0.003 mol / L. If Ag... + If the concentration is too low, the resulting SP@Ag will be... +Insufficient ion conductivity of the membrane leads to high switching voltage and high resistance. Insufficient conductivity also results in unstable conductive channels formed in the device, leading to poor cycle stability. Furthermore, if the doping content is too high, the resulting SP@Ag... + Salt crystals easily precipitate from the membrane, affecting the membrane's structural regularity and surface morphology.

[0033] As a preferred technical solution:

[0034] The preparation process of the PEDOT:PSS film in the self-rectified bio-memristor described above is as follows: First, the PEDOT:PSS suspension is mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate, and then dried to form a PEDOT:PSS precursor film; then, PDMS prepolymer is uniformly coated onto the PEDOT:PSS precursor film and cured to form a PEDOT:PSS / PDMS bilayer film; finally, the PEDOT:PSS / PDMS bilayer film is peeled off from the silicon substrate to obtain a PEDOT:PSS film with PDMS as the substrate.

[0035] The above describes a method for fabricating a self-rectified bio-memristor, SP@Ag + The solution preparation process is as follows: AgNO3 solution and SP solution are mixed evenly at room temperature (24℃) to obtain SP@Ag + Solution;

[0036] The preparation method of SF solution is as follows: raw silk is boiled twice in Na2CO3 aqueous solution, then washed with deionized water, and then the SF is dissolved in LiBr (lithium bromide) solution. The solution is then centrifuged, filtered, dialyzed, and concentrated (i.e., concentrated to 2.0~3.0 wt% at 4℃) to obtain the SF solution. The Na2CO3 aqueous solution contains 0.5 wt% Na2CO3. The relationship between Na2CO3 concentration and degumming rate is non-linear. When the Na2CO3 concentration is in the range of 0.2~0.5 wt%, the degumming rate of SF increases with increasing Na2CO3 concentration. Afterward, even with further increases in Na2CO3 concentration, the degumming rate remains essentially unchanged. Therefore, considering all factors, a Na2CO3 solution with a mass fraction of 0.5 wt% is selected.

[0037] The preparation method of SSP solution is as follows: Spider silk is boiled twice in Na2CO3 aqueous solution and then washed with deionized water to obtain degummed spider silk. The degummed spider silk is then dissolved in NaOH aqueous solution at a mass ratio of 1:50. Without dialysis, the solution is directly filtered and centrifuged to obtain a spider silk protein solution. The mass fraction of Na2CO3 in the Na2CO3 aqueous solution is 0.5 wt%. The relationship between Na2CO3 concentration and degumming rate is non-linear. When the Na2CO3 concentration is in the range of 0.2~0.5 wt%, the degumming rate of SSP increases with increasing Na2CO3 concentration. Afterward, even with further increases in Na2CO3 concentration, the degumming rate remains essentially unchanged. Therefore, considering all factors, a Na2CO3 solution with a mass fraction of 0.5 wt% is selected.

[0038] In the preparation method of the self-rectified bio-memristor described above, the concentration of AgNO3 solution is 0.05 mol / L and the concentration of SP solution is 2.0~3.0 wt%.

[0039] The method for fabricating a self-rectified biomemristor as described above involves depositing an SP@Ag+ functional layer on the surface of the PEDOT:PSS side using a spin-coating method.

[0040] The above-described method for fabricating a self-rectified biomemristor, in SP@Ag + Ag electrode layers are deposited on the film using methods such as thermal evaporation, electron beam evaporation, or magnetron sputtering.

[0041] Invention principle:

[0042] Among the functional materials for memristors, the dielectric properties of the functional layer in memristor devices based on organic materials are generally worse than those based on inorganic materials. Therefore, the realization of the self-rectification characteristics of memristors based on organic materials depends on the synergistic interaction between their electrode materials and functional layers.

[0043] The main components of SP solution are water, protein, amino acids, and some metal ion impurities. An amino acid molecule contains a functional group (carboxyl group) involved in oxygen ions. In addition, as an amphoteric electrolyte, amino acids also have the ability to capture and release protons. Ag + The presence of Ag enhances the ionic conductivity of the SP functional layer. Simultaneously, under external electric field stimulation, Ag... + Ag can accumulate within the SP layer, forming a conductive channel. After the applied electric field is removed, Ag... + It can also spontaneously diffuse within the SP layer, thereby enabling the device to spontaneously switch from a low-resistivity state to a high-resistivity state.

[0044] PEDOT:PSS is a polymer composed of conductive polymer PEDOT and polyelectrolyte PSS bonded together by electrostatic interaction, existing in the form of an aqueous solution. The conductivity of PEDOT:PSS can be improved by doping or post-treatment processes to achieve a conductivity of 10. -3 ~10 3 It has an adjustable conductivity range of S / cm, good mechanical flexibility, compatibility with flexible substrate materials, strong environmental stability, and is not easily oxidized or degraded in air or aqueous solutions.

[0045] The self-rectification characteristics of the device are caused by the synergistic effect of several factors. One is the asymmetry of the electrode work function and the selectivity of carrier injection. The work function of the Ag top electrode is approximately 4.26 eV, while that of the PEDOT:PSS bottom electrode is approximately 4.8–5.2 eV, showing a significant difference. When a forward bias is applied, Ag atoms are easily oxidized to Ag. + Under the influence of the electric field, the electrons migrate towards the PEDOT:PSS side. Simultaneously, the reverse bias lowers the potential barrier for electron injection into the functional layer from the PEDOT:PSS end. Under the influence of the electric field, a small number of electrons can still be successfully injected into the functional layer from the PEDOT:PSS end, allowing the device to conduct smoothly. This "Ag-terminal injection of Ag" technique... + The asymmetric carrier injection mode of "equivalent hole" and "PEDOT:PSS terminal electron injection" forms the basis for forward conduction. Secondly, SP@Ag + Ag within the functional layer + Directional enhancement of migration. SP can interact with Ag via amino groups, hydroxyl groups, etc. + Forming coordinate bonds, for Ag + It acts as an anchoring agent. Under forward bias, the electric field weakens the binding force of the coordination bonds, Ag... + Within the functional layer, the electrodes are arranged along the direction of the electric field, forming a continuous conductive path, which significantly reduces charge transport resistance and promotes forward current conduction. Under reverse bias, the Ag electrode is at a low potential, allowing electrons to be injected from the Ag end, but PEDOT:PSS is at a high potential, and its p-type characteristics strongly suppress electron reverse transport; simultaneously, the Ag in the functional layer... + Influenced by SP coordinate bonds and SO3 in PEDOT:PSS - Electrostatic adsorption prevents reverse migration to form a conductive path, resulting in significant suppression of reverse current. Thirdly, there is the asymmetric difference in interface charge transport. Under forward bias, Ag reacts with Ag within the functional layer... + Forming a "metal-ion" transport interface, Ag + Low injection resistance; PEDOT:PSS and the functional layer form a transition layer through electrostatic interaction, promoting electron injection from the PEDOT:PSS side and migration towards the Ag side, electrons interact with Ag... +Cooperative transport within the functional layer results in high conduction efficiency. Under reverse bias, after electron injection at the Ag end, it needs to migrate across the functional layer to the PEDOT:PSS side. However, the p-type characteristics of PEDOT:PSS inhibit electron transport, and the Ag in the functional layer... + It cannot migrate in the reverse direction to form a conductive channel, the resistance to electron transport is extremely high, and the reverse current is very weak.

[0046] Beneficial effects:

[0047] (1) The preparation method of the present invention is simple, easy to operate and low in cost. The self-rectified biomemristor obtained has the advantages of high rectification ratio and good stability, and realizes the self-rectification characteristics of high rectification ratio.

[0048] (2) The self-rectified bio-memristor of the present invention is beneficial to suppress the generation of leakage current, promote the development of memristor devices towards high efficiency and high density integration, expand the application field of bio-based memristors, and can exhibit different rectification ratios under different limiting currents. At the same time, it also endows SP-based memristors with self-rectification characteristics. Attached Figure Description

[0049] Figure 1 This is a graph showing the IV characteristic curve of the self-rectified biomemristor prepared in Comparative Example 1 of the present invention.

[0050] Figure 2 This is an IV characteristic curve of the self-rectified biomemristor prepared in Example 1 of the present invention;

[0051] Figure 3 This is an IV characteristic curve of the self-rectified biomemristor prepared in Example 3 of the present invention;

[0052] Figure 4 This is a graph showing the IV characteristic curve of the self-rectified biomemristor prepared in Comparative Example 3 of the present invention. Figures 1-4 I in cc Indicates current limitation;

[0053] Figure 5 Examples 1-3, Comparative Examples 1 and 3 of this invention use SF@Ag before and after ethanol immersion. + Schematic diagram of the crystallinity of the membrane. Detailed Implementation

[0054] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0055] To ensure that the performance of the substances used in each embodiment and comparative example is fully disclosed, the manufacturers and brands of the substances are specified. Other products from manufacturers and brands that conform to the limitations of this invention are also feasible.

[0056] The test methods for the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0057] Thickness: The fabricated memristor devices were used as samples, and the cross-section of the samples was obtained by scanning electron microscopy (SEM). The thickness of three different locations in the sample was then measured, and the average value was calculated as the final result.

[0058] Set voltage: Using a 4200A-SCS semiconductor tester, a DC scan cyclic test was performed with a test range of 0V→2V→0V→-2V→0V, a step size of 0.02V, and a current limit of 0.1mA. The IV characteristic curve was analyzed, and the voltage at which the current just reached the current limit during the first 0V→2V scan was taken as the set voltage. During the test, 25 different locations were selected for the same sample and tested one by one. The minimum and maximum values ​​among these 25 test results were used as the final value range.

[0059] Reset voltage: A 4200A-SCS semiconductor tester was used with DC scanning cyclic testing. The test range was 0V→2V→0V→-2V→0V, with a step size of 0.02V and a current limit of 0.1mA. The IV characteristic curve was analyzed, and the voltage at which the current just fell below the current limit during the second 2V→0V scan was taken as the reset voltage. During the test, 25 different locations were selected for the same sample and tested one by one. The minimum and maximum values ​​among these 25 test results were used as the final value range.

[0060] Low-resistance state resistance: A 4200A-SCS semiconductor tester was used with DC scanning cyclic testing. The test range was 0V→2V→0V→-2V→0V, with a step size of 0.02V and a current limit of 0.1mA. The IV characteristic curve was analyzed, and the ratio of voltage to current at the set voltage was taken as the low-resistance state resistance. During the test, 25 different locations were selected for testing the same sample one by one, and the minimum and maximum values ​​among these 25 test results were taken as the final value range.

[0061] High-resistivity value: A 4200A-SCS semiconductor tester was used with DC scanning cyclic testing. The test range was 0V→2V→0V→-2V→0V, with a step size of 0.02V and a current limit of 0.1mA. The IV characteristic curve was analyzed, and the ratio of voltage to current at the reset voltage was taken as the high-resistivity value. During the test, 25 different locations were selected for testing the same sample one by one, and the minimum and maximum values ​​among these 25 test results were taken as the final value range.

[0062] Rectification ratio: A 4200A-SCS semiconductor tester was used with DC scanning cycle testing. The test range was 0V→2V→0V→-2V→0V, with a step size of 0.02V and a current limit of 0.1mA. The IV characteristic curve was analyzed, and the ratio of the "voltage to current ratio at the set voltage" to the "voltage to current ratio at the voltage that is the opposite of the set voltage" was taken as the rectification ratio. During the test, 25 different parts of the same sample were selected and tested one by one. The minimum and maximum values ​​among these 25 test results were used as the final value range.

[0063] Example 1

[0064] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0065] (1) Preparation of PEDOT:PSS membrane;

[0066] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, p-type conductivity, crystal orientation) is... <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0067] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0068] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.20 μm and a PDMS film thickness of 0.5 mm.

[0069] (2) Preparation of SF@Ag + Solution;

[0070] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4 °C to obtain a 2 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0071] (2.2) After mixing 0.05 mol / L AgNO3 aqueous solution with SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF4 solution in a volume ratio of 0.02:1.

[0072] The obtained SF@Ag + Ag in solution + The concentration was 0.001 mol / L;

[0073] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated in two stages. The first stage had a spin-coating speed of 500 rpm and a spin-coating time of 5 s. The second stage had a spin-coating speed of 2000 rpm and a spin-coating time of 25 s.

[0074] (4) PEDOT: After spin-coating one side of the PSS film, it is immersed in ethanol for 30 min and then dried for 30 min to form SF@Ag. + The membrane was finally deposited on SF@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0075] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0076] The bottom electrode layer is a PEDOT:PSS film;

[0077] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 54.8% and a thickness of 75 nm.

[0078] The top electrode layer is an Ag electrode with a thickness of 100 nm;

[0079] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.82 to 1.04 V, the reset voltage is 0.52 to 0.58V, and the low-resistance state resistance is 9.0 × 10⁻⁶.3 ~4.0×10 4 Ω, high-resistance state resistance is 8.0×10 7 ~4.0×10 8 Ω, rectification ratio is 2.2×10 3 ~8.6×10 3 .

[0080] Comparative Example 1

[0081] A method for preparing a self-rectified bio-memristor is basically the same as in Example 1, except that the AgNO3 aqueous solution in step (2.2) is replaced with an equal mass of SF solution.

[0082] The final self-rectified bio-memristor is basically the same as in Example 1, except that the memristor functional layer is an SF film with a crystallinity of 53.3%.

[0083] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0~2.0V, the self-rectified bio-memristor exhibits no significant set voltage and no significant reset voltage, with a low-resistance value of 9.0×10⁻⁶. 4 ~1.0×10 5 Ω, rectification ratio is 200~800.

[0084] Comparing Comparative Example 1 and Example 1, it can be seen that the self-rectified bio-memristor prepared in this comparative example has no obvious set voltage and reset voltage, a relatively high resistance in the low-resistance state, and a relatively low rectification ratio. This is because the memristor functional layer in this comparative example is an SF film, while a pure SF film does not contain Ag. + When a positive voltage is applied, Ag can only be generated through the ionization of the Ag electrode. + The Ag produced + It needs to migrate to the PEDOT:PSS terminal under the action of an electric field to form a conductive path, which results in a high low-resistance value and a low rectification ratio of the self-rectified bio-memristor in this comparative example.

[0085] Comparative Example 2

[0086] A method for preparing a self-rectified bio-memristor is basically the same as in Example 1, except that the volume ratio of AgNO3 aqueous solution to SF solution in step (2.2) is 0.01:1, so that the obtained SF@Ag + Ag in solution + The concentration is 0.0005 mol / L.

[0087] The final self-rectified bio-memristor is basically the same as in Example 1, except that: SF@Ag + The crystallinity of the membrane is 53.8%;

[0088] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0~2.0V, the self-rectified bio-memristor exhibits no significant set voltage, no significant reset voltage, and a low-resistance value of 2.0×10⁻⁶. 4 ~5.0×10 4 Ω.

[0089] Comparing Comparative Example 2 with Example 1, it can be seen that the self-rectified bio-memristor prepared in this comparative example has no obvious set voltage and reset voltage, and the low-resistance state resistance is relatively high. This is because, compared with Example 1, the Ag in Comparative Example 2... + With a doping concentration of only 0.0005 mol / L, when a positive voltage is applied, the Ag in the film... + Similarly, Ag will migrate and accumulate along the direction of the electric field to form conductive channels, but the Ag inside the film... + The lower content results in a finer conductive channel compared to Example 1, making it easier for spontaneous diffusion to occur. This ultimately leads to a higher low-resistance value and poorer cycle stability in the self-rectified biomemristor.

[0090] Comparative Example 3

[0091] A method for preparing a self-rectified bio-memristor is basically the same as in Example 1, except that the mass ratio of AgNO3 aqueous solution to SF solution in step (2.2) is 0.087:1, so that the obtained SF@Ag + Ag in solution + The concentration was 0.004 mol / L.

[0092] The final self-rectified bio-memristor is basically the same as in Example 1, except that: SF@Ag + The crystallinity of the membrane is 53.1%;

[0093] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.44 to 0.49V, the reset voltage is -0.18 to 0.12V, and the low-resistance state resistance is 2.0 × 10⁻⁶. 3 ~3.0×10 3 Ω, high resistance is 7.0 × 10 Ω. 5 ~1.0×10 6 Ω, loses self-rectification characteristics.

[0094] Comparing Example 1 and Comparative Example 3, it can be seen that the self-rectifying bio-memristor prepared in this comparative example has lower set voltage and reset voltage, lower resistance values ​​in both low-resistance and high / low-resistance states, and loses its self-rectifying characteristics. This is because the Ag in this comparative example... + With a high doping concentration, when a forward voltage is applied, the Ag in the film... + Similarly, they migrate and aggregate along the direction of the electric field to form conductive channels, but due to the Ag within the membrane...+ The higher content of Ag makes it easier to form conductive channels, resulting in a lower settling voltage and a more stable conductive channel compared to Example 1, leading to a lower resistance value in the low-resistance state. Furthermore, after the positive voltage is removed, the Ag content in the conductive channel increases. + Unable to spontaneously diffuse, the self-rectified bio-memristor remains in a low-resistance state. When a reverse voltage is applied, charge carriers can still migrate smoothly through the conductive channel, causing the self-rectified bio-memristor to lose its self-rectification characteristics. After the reverse voltage exceeds a certain value (i.e., the reset voltage), SF@Ag... + The conductive channels within the functional layer break, and the self-rectified biomemristor returns to a high-resistivity state, but due to the Ag within the membrane... + Excessive Ag content + Diffusion is difficult and the conductive channel is not completely broken, but it can still help the carriers migrate between the Ag electrode and the PEDOT:PSS electrode, which ultimately leads to a low high-resistivity value of the self-rectified biomemristor.

[0095] Example 2

[0096] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0097] (1) Preparation of PEDOT:PSS membrane;

[0098] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, p-type conductivity, crystal orientation) is... <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0099] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 20 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0100] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.10 μm and a PDMS film thickness of 0.5 mm.

[0101] (2) Preparation of SF@Ag + Solution;

[0102] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4°C to obtain a 2 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0103] (2.2) After mixing 0.05 mol / L AgNO3 aqueous solution with SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF solution with a volume ratio of 0.042:1.

[0104] The obtained SF@Ag + Ag in solution + The concentration was 0.002 mol / L;

[0105] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated in two stages. The first stage had a spin-coating speed of 500 rpm and a spin-coating time of 5 s. The second stage had a spin-coating speed of 2000 rpm and a spin-coating time of 25 s.

[0106] (4) PEDOT: After spin-coating one side of the PSS film, it is immersed in ethanol for 30 min and then dried for 30 min to form SF@Ag. + The membrane was finally deposited on SF@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0107] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0108] The bottom electrode layer is a PEDOT:PSS film;

[0109] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 57.4% and a thickness of 70 nm.

[0110] The top electrode layer is an Ag electrode with a thickness of 110 nm;

[0111] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.76 to 0.84V, the reset voltage is 0.46 to 0.52V, and the low-resistance state resistance is 8.3 × 10⁻⁶. 3 ~1.2×10 4 Ω, high resistance is 7.0 × 10 Ω. 7 ~1.2×10 8 Ω, rectification ratio is 4.1×10 3 ~8.0×10 3 .

[0112] Example 3

[0113] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0114] (1) Preparation of PEDOT:PSS membrane;

[0115] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, p-type conductivity, crystal orientation) is... <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0116] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 60 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0117] The obtained PEDOT:PSS film with polydimethylsiloxane as the substrate has a thickness of 0.95 μm and a PDMS film thickness of 0.5 mm.

[0118] (2) Preparation of SF@Ag + Solution;

[0119] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4°C to obtain a 3 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0120] (2.2) After mixing a 0.05 mol / L aqueous solution of AgNO3 with an SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF4 solution in a volume ratio of 0.064:1.

[0121] The obtained SF@Ag + Ag in solution + The concentration was 0.003 mol / L;

[0122] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated in two stages. The first stage had a spin-coating speed of 500 rpm and a spin-coating time of 5 s. The second stage had a spin-coating speed of 2000 rpm and a spin-coating time of 25 s.

[0123] (4) PEDOT: After spin-coating one side of the PSS film, it is immersed in ethanol for 30 min and then dried for 30 min to form SF@Ag. + The membrane was finally deposited on SF@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0124] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0125] The bottom electrode layer is a PEDOT:PSS film;

[0126] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 57.8% and a thickness of 90 nm.

[0127] The top electrode layer is an Ag electrode with a thickness of 110 nm;

[0128] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.68 to 0.72V, the reset voltage is 0.44 to 0.5V, and the low-resistance state resistance is 8.0 × 10⁻⁶. 3 ~1.0×10 4 Ω, high-resistance state resistance is 1.0×10 8 ~4.0×10 8 Ω, rectification ratio is 5.3×10 3 ~1.7×10 4 .

[0129] like Figure 5 As shown, SF@Ag in Examples 1-3, Comparative Examples 1 and 3 were soaked in ethanol before and after treatment. + A comparison of the crystallinity of the membranes shows that, with Ag... + Increasing the doping concentration slightly improved the crystallinity of the SF film, but when the doping concentration exceeded 3 mmol / L, the Ag... + Salt crystals precipitate from the SF membrane, disrupting the structural integrity of the SF membrane and reducing its crystallinity.

[0130] The self-rectified bio-memristors of Examples 1, 3, Comparative Example 1, and 3 were subjected to IV characteristic curve testing (the self-rectified bio-memristors of Examples 1, 3, and Comparative Example 1 were cycled 50 times, and the self-rectified bio-memristor of Comparative Example 3 was cycled 10 times, with each cycle being 0V→2V→0V→-2V→0V). The results are as follows. Figures 1-4 As shown in the figure, in Examples 1 and 3, due to Ag + Doping improves the conductivity of the functional layer, thereby reducing the overall operating voltage of the device, while Ag... + With a suitable doping concentration, the cycling stability of the device is improved to a certain extent; however, the self-rectified bio-memristors in Comparative Examples 1 and 3 show a lower degree of curve overlap during operation, indicating that their cycling stability is also poor.

[0131] Example 4

[0132] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0133] (1) Preparation of PEDOT:PSS membrane;

[0134] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, p-type conductivity, crystal orientation) is... <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0135] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0136] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.05 μm and a PDMS film thickness of 0.5 mm.

[0137] (2) Preparation of SF@Ag + Solution;

[0138] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4°C to obtain a 2.5 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0139] (2.2) After mixing 0.05 mol / L AgNO3 aqueous solution with SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF solution with a volume ratio of 0.042:1.

[0140] The obtained SF@Ag + Ag in solution + The concentration was 0.002 mol / L;

[0141] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated in two stages. The first stage had a spin-coating speed of 550 rpm and a spin-coating time of 7 s. The second stage had a spin-coating speed of 2200 rpm and a spin-coating time of 27 s.

[0142] (4) PEDOT: After spin-coating one side of the PSS film, it is immersed in ethanol for 45 min and then dried for 35 min to form SF@Ag. + The membrane was finally deposited on SF@Ag using a thermal evaporation method. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0143] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0144] The bottom electrode layer is a PEDOT:PSS film;

[0145] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 57.4% and a thickness of 75 nm.

[0146] The top electrode layer is an Ag electrode with a thickness of 120 nm;

[0147] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.74 to 0.80V, the reset voltage is 0.44 to 0.48V, and the low-resistance state resistance is 5.6 × 10⁻⁶. 3 ~9.0×10 3 Ω, high-resistance state resistance is 3.0×10 7 ~9.0×10 7 Ω, rectification ratio is 1.3×10 3 ~5.2×10 3 .

[0148] Example 5

[0149] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0150] (1) Preparation of PEDOT:PSS membrane;

[0151] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, p-type conductivity, crystal orientation) is... <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0152] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0153] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.05 μm and a PDMS film thickness of 0.5 mm.

[0154] (2) Preparation of SF@Ag + Solution;

[0155] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4°C to obtain a 3 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0156] (2.2) After mixing 0.05 mol / L AgNO3 aqueous solution with SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF4 solution in a volume ratio of 0.064:1.

[0157] The obtained SF@Ag + Ag in solution + The concentration was 0.003 mol / L;

[0158] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated in two stages. The first stage had a spin-coating speed of 600 rpm and a spin-coating time of 10 s. The second stage had a spin-coating speed of 2500 rpm and a spin-coating time of 30 s.

[0159] (4) PEDOT: After spin-coating one side of the PSS film, it was immersed in ethanol for 60 min and then dried for 40 min to form SF@Ag. + The film was finally deposited on SF@Ag using magnetron sputtering. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0160] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0161] The bottom electrode layer is a PEDOT:PSS film;

[0162] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 57.8% and a thickness of 80 nm.

[0163] The top electrode layer is an Ag electrode with a thickness of 115 nm;

[0164] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.70 to 0.76V, the reset voltage is 0.38 to 0.42V, and the low-resistance state resistance is 9.0 × 10⁻⁶. 3 ~1.0×10 4 Ω, the high-resistance state resistance is 8.2 × 10 Ω. 7 ~2.0×10 8 Ω, rectification ratio is 6.6×10 3 ~1.2×10 4 .

[0165] Example 6

[0166] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0167] (1) Preparation of PEDOT:PSS membrane;

[0168] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, with p-type conductivity and crystal orientation of ) is used. <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0169] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0170] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 0.9 μm and a PDMS film thickness of 0.5 mm.

[0171] (2) Preparation of SF@Ag + Solution;

[0172] (2.1) The raw silk was boiled twice in a Na2CO3 aqueous solution, then washed with deionized water to obtain SF. The SF was then dissolved in a 9.3 mol / L lithium bromide aqueous solution, centrifuged, filtered, dialyzed, and concentrated at 4°C to obtain a 2 wt% SF solution; wherein the mass fraction of Na2CO3 in the Na2CO3 aqueous solution was 0.5 wt%.

[0173] (2.2) After mixing 0.05 mol / L AgNO3 aqueous solution with SF solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SF@Ag + The solution contains an aqueous solution of AgNO3 and an SF4 solution in a volume ratio of 0.02:1.

[0174] The obtained SF@Ag + Ag in solution + The concentration was 0.001 mol / L;

[0175] (3) Spin-coating SF@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated at a speed of 2000 rpm for 30 seconds.

[0176] (4) PEDOT: After spin-coating one side of the PSS film, it is immersed in ethanol for 30 min and then dried for 30 min to form SF@Ag.+ The membrane was finally deposited on SF@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0177] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0178] The bottom electrode layer is a PEDOT:PSS film;

[0179] The memristor functional layer is SF@Ag + Membrane, SF@Ag + Membrane refers to Ag + The doped SF film has a crystallinity of 54.8% and a thickness of 75 nm.

[0180] The top electrode layer is an Ag electrode with a thickness of 105 nm;

[0181] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.84 to 1.20V, the reset voltage is 0.52 to 0.64V, and the low-resistance state resistance is 5.4 × 10⁻⁶. 3 ~4.2×10 4 Ω, high-resistance state resistance is 9.6×10 Ω. 7 ~4.1×10 8 Ω, rectification ratio is 1.7×10 3 ~9.7×10 3 .

[0182] Example 7

[0183] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0184] (1) Preparation of PEDOT:PSS membrane;

[0185] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, with p-type conductivity and crystal orientation of ) is used. <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0186] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0187] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.0 μm and a PDMS film thickness of 0.5 mm.

[0188] (2) Preparation of SSP@Ag + Solution;

[0189] (2.1) After boiling the spider silk twice in a Na2CO3 aqueous solution, it is washed with deionized water to obtain degummed spider silk. The degummed spider silk is dissolved in a NaOH aqueous solution at a mass ratio of 1:50. Without dialysis, it is directly filtered and centrifuged to obtain a spider silk protein solution with a concentration of 2wt%. The mass fraction of Na2CO3 in the Na2CO3 aqueous solution is 0.5wt%.

[0190] (2.2) After mixing the 0.05 mol / L AgNO3 aqueous solution with the SSP solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SSP@Ag + The solution contains an aqueous solution of AgNO3 and an SSP solution in a volume ratio of 0.02:1.

[0191] The obtained SSP@Ag + Ag in solution + The concentration was 0.001 mol / L;

[0192] (3) Spin-coating SSP@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated at a speed of 1000 rpm for 10 seconds, and then spin-coated twice.

[0193] (4) PEDOT: After spin-coating one side of the PSS film, it was immersed in ethanol for 30 min and then dried for 30 min to form SSP@Ag. + The membrane was finally deposited on SSP@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0194] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0195] The bottom electrode layer is a PEDOT:PSS film;

[0196] The memristor functional layer is SSP@Ag + Membrane, SSP@Ag + Membrane refers to Ag + The doped SSP film has a crystallinity of 52% and a thickness of 75 nm.

[0197] The top electrode layer is an Ag electrode with a thickness of 100 nm;

[0198] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.86 to 1.12V, the reset voltage is 0.54 to 0.62V, and the low-resistance state resistance is 6.2 × 10⁻⁶. 3 ~1.4×10 4 Ω, high resistance state resistance is 8.0×10 7 ~2.1×10 8 Ω, rectification ratio is 1.3×10 3 ~1.5×10 4 .

[0199] Example 8

[0200] A method for fabricating a self-rectified bio-memristor, comprising the following steps:

[0201] (1) Preparation of PEDOT:PSS membrane;

[0202] (1.1) The silicon substrate (manufactured by the 46th Research Institute of China Electronics Technology Group Corporation, with p-type conductivity and crystal orientation of ) is used. <111> The silicon substrate (with a diameter of φ76.2mm) was sequentially cleaned with water, ethanol, and water using ultrasonic cleaning, and then treated with 500W oxygen plasma for 10 minutes to obtain a hydrophilic silicon substrate.

[0203] (1.2) PEDOT:PSS suspension (manufacturer: Shanghai Jingnian Chemical Co., Ltd., specification: CleviosPH1000, solid content: 1.1%) was mixed with ethylene glycol and uniformly coated onto a hydrophilically treated silicon substrate. The mixture was then dried at 60°C for 30 min to form a PEDOT:PSS precursor film. Polydimethylsiloxane prepolymer (manufacturer: Dow Chemical Company, specification: SYLGARD™ 184 Silicone Elastomer Kit) was then uniformly coated onto the PEDOT:PSS precursor film and cured at 60°C for 2 h to form a PEDOT:PSS / PDMS bilayer film. The PEDOT:PSS / PDMS bilayer film was then peeled off from the silicon substrate to obtain a PEDOT:PSS film with polydimethylsiloxane as the substrate. The volume ratio of PEDOT:PSS suspension to ethylene glycol was 100:2.

[0204] The obtained PEDOT:PSS film with polydimethylsiloxane as substrate has a thickness of 1.0 μm and a PDMS film thickness of 0.5 mm.

[0205] (2) Preparation of SSP@Ag + Solution;

[0206] (2.1) After boiling the spider silk twice in a Na2CO3 aqueous solution, it is washed with deionized water to obtain degummed spider silk. The degummed spider silk is dissolved in a NaOH aqueous solution at a mass ratio of 1:50. Without dialysis, it is directly filtered and centrifuged to obtain a spider silk protein solution with a concentration of 2.5 wt%. The mass fraction of Na2CO3 in the Na2CO3 aqueous solution is 0.5 wt%.

[0207] (2.2) After mixing the 0.05 mol / L AgNO3 aqueous solution with the SSP solution, the mixture was stirred at 150 rpm for 30 min at 24 °C to obtain SSP@Ag + The solution contains an aqueous solution of AgNO3 and an SSP solution in a volume ratio of 0.064:1.

[0208] The obtained SSP@Ag + Ag in solution + The concentration was 0.003 mol / L;

[0209] (3) Spin-coating SSP@Ag onto one side of the PEDOT:PSS membrane. + The solution was spin-coated at a speed of 1500 rpm for 15 seconds, and then spin-coated twice.

[0210] (4) PEDOT: After spin-coating one side of the PSS film, it was immersed in ethanol for 30 min and then dried for 30 min to form SSP@Ag. + The membrane was finally deposited on SSP@Ag using electron beam evaporation. + A self-rectifying biomemristor was fabricated by depositing an Ag electrode layer on the membrane.

[0211] The final self-rectified bio-memristor consists of a bottom electrode layer, a memristor functional layer, and a top electrode layer, which are sequentially composited.

[0212] The bottom electrode layer is a PEDOT:PSS film;

[0213] The memristor functional layer is SSP@Ag + Membrane, SSP@Ag + Membrane refers to Ag + The doped SSP film has a crystallinity of 53.5% and a thickness of 70 nm.

[0214] The top electrode layer is an Ag electrode with a thickness of 110 nm;

[0215] Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.60 to 0.82V, the reset voltage is 0.30 to 0.44V, and the low-resistance state resistance is 5.0 × 10⁻⁶. 3 ~1.2×10 4 Ω, high-resistance state resistance is 2.0×10 7 ~1.1×10 8 Ω, rectification ratio is 4.0×10 3 ~9.0×10 3 .

Claims

1. A self-rectified bio-memristor, comprising a sequentially composited bottom electrode layer, a memristor functional layer, and a top electrode layer, characterized in that: The bottom electrode layer is a PEDOT:PSS film, and the memristor functional layer is SP@Ag. + membrane; SP@Ag + Membrane refers to Ag + Doped silk protein membrane or Ag + Doped spider silk protein membrane; SP@Ag + The membrane is made by spin-coating SP@Ag onto one side of a PEDOT:PSS membrane. + The solution is then soaked in ethanol and dried to form the solution. The preparation process of PEDOT:PSS film is as follows: First, PEDOT:PSS suspension is mixed with ethylene glycol and uniformly coated on a hydrophilically treated silicon substrate, and then dried to form PEDOT:PSS precursor film; then, polydimethylsiloxane prepolymer is uniformly coated on PEDOT:PSS precursor film and cured to form PEDOT:PSS / PDMS bilayer film; finally, PEDOT:PSS / PDMS bilayer film is peeled off from silicon substrate to obtain PEDOT:PSS film with PDMS as substrate. SP@Ag + The solution preparation process is as follows: AgNO3 solution and SP solution are mixed evenly at room temperature to obtain SP@Ag + Solution; Under conditions of a current limit of 0.1mA and a voltage test range of -2.0 to 2.0V, the set voltage of the self-rectified bio-memristor is 0.60 to 1.20V, the reset voltage is 0.30 to 0.64V, and the low-resistance state resistance is 5.0 × 10⁻⁶. 3 ~4.2×10 4 Ω, high-resistance state resistance is 2.0×10 7 ~4.1×10 8 Ω, rectification ratio is 1.3×10 3 ~1.7×10 4 .

2. The self-rectified bio-memristor according to claim 1, characterized in that, SP@Ag + The crystallinity of the membrane is 52.0~57.8%.

3. A self-rectified bio-memristor according to claim 1, characterized in that, The top electrode layer is an Ag electrode.

4. A self-rectified bio-memristor according to claim 1, characterized in that, The thickness of the top electrode layer is 100~120 nm, the thickness of the memristor functional layer is 60~90 nm, and the thickness of the bottom electrode layer is 0.9~1.2 μm.

5. A method for fabricating a self-rectified bio-memristor as described in any one of claims 1 to 4, characterized in that: First, SP@Ag is spin-coated onto one side of the PEDOT:PSS film. + The solution was then soaked in ethanol and dried to form SP@Ag. + The membrane, finally in SP@Ag + A self-rectified biomemristor was fabricated by depositing an Ag electrode layer on the membrane. SP@Ag + Ag in solution + The concentration is 0.001~0.003 mol / L.

6. The method for fabricating a self-rectified bio-memristor according to claim 5, characterized in that, The concentration of AgNO3 solution is 0.05 mol / L, and the concentration of SP solution is 2.0~3.0 wt%.

7. The method for fabricating a self-rectified bio-memristor according to claim 5, characterized in that, In SP@Ag + Ag electrode layers are deposited on the film using methods such as thermal evaporation, electron beam evaporation, or magnetron sputtering.